Rough Set and Knowledge Technology 5th International Conference, RSKT 2010, Beijing, China, October 15-17, 2010. Proceedings - Yu, Jian.; Greco, Salvatore.; Lingras, Pawan.; Wang, Guoyin.; Skowron, Andrzej. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the 5th International Conference on Rough Set and Knowledge Technology, RSKT 2010, held in Beijing, China, in October 2010. The 98 revised full papers papers presented were carefully reviewed and selected from 175 initial submissions. The papers are organized in topical sections on rough sets and computing theory, fuzzy sets, knowledge technology, intelligent information processing, health informatics and biometrics authentication, neural networks, complex networks, granular computing, metaheuristic, cloud model and its application, data mining in cloud computing, decision-theoretic rough set model, and quotient space theory research and application.